2018
DOI: 10.1055/a-0660-0236
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology Uncovers Anticancer Activity of Mammea-Type Coumarins from Calophyllum brasiliense

Abstract: Mammea-type coumarins are a particular type of secondary metabolites biosynthesized by the tropical rainforest tree , which is distributed from South America to Mexico. Particularly, mammea A/BA and A/BB (alone or as a mixture) possess biological properties such as cytotoxic and antitumoral activities, however, most of its molecular targets remain unknown. In this context, novel bioinformatic approaches, such as network pharmacology analysis, have been successfully used in herbal medicine to accelerate researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Based on the substituent at C-4, there are so far five designated series: mammea A (4-fenil), B (4-propil), C (4-pentil), D [4-(1-metilpropil)], and E (1-acetoxipropil) ( Crombie et al, 1987 ). These types of coumarins are biologically active with antiprotozoal activity against Leishmania amazonensis ( Brenzan et al, 2007 , 2012 ), L. brasiliensis ( Honda et al, 2010 ) and Trypanosoma cruzi ( Reyes-Chilpa et al, 2008 ); cytotoxic activity ( Reyes-Chilpa et al, 2004 ; Ito et al, 2006 ; Du et al, 2010 ; Gómez-Verjan et al, 2019 ), and others have shown good activity against dengue and chikungunya viruses ( Gómez-Calderón et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the substituent at C-4, there are so far five designated series: mammea A (4-fenil), B (4-propil), C (4-pentil), D [4-(1-metilpropil)], and E (1-acetoxipropil) ( Crombie et al, 1987 ). These types of coumarins are biologically active with antiprotozoal activity against Leishmania amazonensis ( Brenzan et al, 2007 , 2012 ), L. brasiliensis ( Honda et al, 2010 ) and Trypanosoma cruzi ( Reyes-Chilpa et al, 2008 ); cytotoxic activity ( Reyes-Chilpa et al, 2004 ; Ito et al, 2006 ; Du et al, 2010 ; Gómez-Verjan et al, 2019 ), and others have shown good activity against dengue and chikungunya viruses ( Gómez-Calderón et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology is an emerging discipline of “drug‐target‐disease” relationship network based on systems biology and multidirectional pharmacology, which is used to systematically and comprehensively observe the impact of drugs on disease networks 10 . Accumulating researches have proved that network pharmacology is a feasible systematic approach to uncovering the molecular mechanisms by which drugs exert physiological effects or to searching for small molecule drugs that may have therapeutic effects 11,12 . In this study, we used network pharmacology combined with laboratory methods to explore the possible molecular mechanism of the anti‐tumor effect of SchA.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Accumulating researches have proved that network pharmacology is a feasible systematic approach to uncovering the molecular mechanisms by which drugs exert physiological effects or to searching for small molecule drugs that may have therapeutic effects. 11 , 12 In this study, we used network pharmacology combined with laboratory methods to explore the possible molecular mechanism of the anti‐tumor effect of SchA.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are often used to discover new mechanisms of action and possible adverse effects of drugs 8 . Several research groups have used network pharmacology for different application, for instance, to explore bioactive ethnobotanical compounds with known use and to repurpose them for other pharmacological use 11,12 . Other example is metformin that has been repurposed as a chemo-preventive drug and is already on clinical trials 13 .…”
Section: Introductionmentioning
confidence: 99%